Incidencia del uso de las herramientas didácticas tecnológicas en el proceso enseñanza –aprendizaje de los estudiantes de los octavos, novenos y decimos años de educación general básica de la Unidad Educativa Santa Teresita de la ciudad de Santa Rosa en el periodo lectivo 2012-2013. - Márquez Córdova, Jessica Grace (2016)
The research called incidence of use of the tools Didactic Technology In The -Learning of students in the eighth, ninth and tenth years of general education Basic Education Process, was conducted by analyzing posing education through TIC’s, this is due to the situation in which are the elements that make up the field of education, lack of training teachers in the use of TIC’s as a tool for their classroom practices, the change in the learning process, students in the proper use of these tools that contribute to improving the academic performance of students, have adequate infrastructure and tools to complement the use of TIC’s in the classroom.